CREATIVE TECHNOLOGY AS A DRIVER OF SOCIO-PRENEURSHIP: ENTREPRENEURIAL RESPONSES TO GLOBAL CHALLENGES - Wong, Lucas; Lim, Sofia; Brown, Sarah; Alimuddin, Alimuddin (Journal of Social Entrepreneurship and Creative Technology, 2026)
The increasing complexity of global challenges such as poverty, climate change, and inequality has pushed marginalized communities to seek innovative solutions through entrepreneurship. Creative technologies like virtual reality (VR), augmented reality (AR), and mobile applications offer novel opportunities for socio-preneurship, enabling entrepreneurs to develop solutions that promote social, environmental, and economic sustainability. This study explores how creative technologies serve as a catalyst for socio-preneurship by examining the experiences of entrepreneurs in underserved regions who have integrated these technologies into their business models. The research aims to understand how these technologies empower entrepreneurs to overcome systemic barriers and create scalable solutions to global challenges. A mixed-methods approach was utilized, combining qualitative interviews and quantitative surveys to gather insights from 20 entrepreneurs across diverse sectors, including education, healthcare, and agriculture. The findings suggest that creative technology enhances business performance, expands market access, and strengthens community ties. Moreover, social capital was identified as a crucial factor in amplifying the impact of technology adoption. The study concludes that creative technology is essential for inclusive socio-preneurship, offering a pathway to address global challenges while fostering local economic and social development. Policy recommendations include supporting technological infrastructure and social networks for marginalized entrepreneurs to ensure sustainable growth.